Normalisasi Penggunaan Umpatan Kata Hewan Sebagai Penanda Kedekatan Relasional Dalam Komunikasi Generasi Z - Sofi Indras Tuti; Naailah Haniifah; Ike Desi Florina (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Among contemporary youth, particularly Generation Z, which currently constitutes a significant proportion of Indonesia’s population, everyday communication patterns have become increasingly relaxed, expressive, and adaptive to linguistic change. One prominent phenomenon within this group is the use of animal-related swear words, which are no longer perceived solely as negative expressions but have become integrated into everyday communicative practices. This study adopts a descriptive qualitative method with a phenomenological approach to examine how such expressions are interpreted within interpersonal relationships. Drawing upon Social Penetration Theory, the study explores the function of animal-based swear words in informal communication as indicators of familiarity, comfort, and relational closeness. However, when the use of such expressions is not aligned with the depth of interpersonal relationships, it may result in violations of social norms or ethical standards and potentially lead to social or legal consequences. The findings reveal a semantic shift, commonly associated with pejoration, in which swear words are no longer used merely as emotional outbursts but also function as communicative resources that reflect relational openness, facilitate intimacy, and contribute to changes in the boundaries of politeness norms in Generation Z communication.